Pengaruh Pertumbuhan Pendapatan, Kebijakan Dividen, Kebijakan Hutang, Ukuran Perusahaan dan Kinerja Perusahaan terhadap Nilai Perusahaan Infrastruktur yang Terdaftar di BEI - Felix Liong; Irvania Cherry; Sheyla Tri Vanny (INOVASI, 2023)
The purpose of this research is to analyze the effect of sales growth, dividend policy, debt policy, companyâ€™s size, and companyâ€™s performance to infrastructureâ€™s company value listed in Indonesia Exchange Stocks. The method of this research is clause method and use the purposive sampling method as the method to sampling the researchâ€™s population. The total of this researchâ€™s sample is 26 company. The result of the hypothesis test of the sales growth is the sales growth doesnâ€™t affect the companyâ€™s value. The result is   t-test 0.477 < t-table 1,666462. The result of the hypothesis test of the dividend policy is the dividend policy doesnâ€™t affect the companyâ€™s value. The result is t-test 0.6389 < t-table 1,666462. The result of the hypothesis test of the debt policy is the debt policy affect the companyâ€™s value positively significant. The result is t-test 3,956 > t-table 1,666462. The result of the hypothesis test of the companyâ€™s size is the companyâ€™s size affect the companyâ€™s value positively significant The result is t-test 6,083 > t-table 1,666462. The result of the hypothesis test of the companyâ€™s performance is the companyâ€™s performance doesnâ€™t affect the companyâ€™s value The result is t-test 1,080 < t-table 1,666462. The result of simultaneously test is sales growth, dividend policy, debt policy, companyâ€™s size, companyâ€™s performance affects the companyâ€™s value, with the test result is F-test 5,607862 > F-table 2,332.